165k views
1 vote
Solve for x................

Solve for x................-example-1
User Gakio
by
5.4k points

2 Answers

4 votes

Answer:

Choice C is correct answer.

Explanation:

Given equation is :

x²-2x-11= 0

ax²+bx+c = 0 is general quadratic equation.

x = (-b±√b²-4ac) / 2a is quadratic formula to solve quadratic equation.

Comparing general equation with given equation,we get

a = 1 , b = -2 and c = -11

Putting above values in quadratic formula ,we get

x = (-(-2)±√(-2)²-4(1)(-11)) / 2(1)

x = (2±√4+44) / 2

x = (2±√48) / 2

x = (2±4√3) / 2

x = 2(1±2√3) / 2

x = 1±2√3

Hence, the solution of x²-2x-11 =0 is 1±2√3.


User Tippi
by
6.0k points
4 votes

Answer:

Option C


x={1(+/-)2√(3)}


Explanation:

we have


x^(2)-2x-11=0

we know that


The formula to solve a quadratic equation of the form
ax^(2) +bx+c=0 is equal to



x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}


in this problem we have



x^(2)-2x-11=0

so



a=1\\b=-2\\c=-11


substitute


x=\frac{-(-2)(+/-)\sqrt{-2^(2)-4(1)(-11)}} {2(1)}



x=\frac{2(+/-)√(4+44)} {2}



x=\frac{2(+/-)√(48)} {2}



x=\frac{2(+/-)4√(3)} {2}



x={1(+/-)2√(3)}


User Elias Naur
by
5.2k points